PERENCANAAN DAN KALIBRASIBATANGPELURUS BERDASARKANSTANDARJISB7514 - Joko Prihartono; Purwo Subekti (Jurnal APTEK, 2014)
In the measurement process on a machine tool alignment required an alignment as the reference standard.In this case the rod straightener is a measurement tool that is commonly used in metrology laboratories. Inplanning and the alignment rod calibration followed standard JIS B7514, which is described in the standardspecification of the alignment rod which include dimensions, quality and tolerance limits. From the results ofthe calibration are performed on the alignment rod has a classification according to JIS B7514 standardclass (grade) B. Thus the alignment rod can only be used for testing machine tools with high level ofaccuracy that is not high (conventional).